Dating and Relationships under a Bluesky: An Educational Data Science Perspective on Communication on BlueSky - Rehm, Martin; Muth Andersen, Elisabeth (Proceedings of the International Conference on Networked Learning, 2026)
Social media platforms increasingly play a central role in how individuals acquire knowledge, form expectations, and negotiate practices surrounding intimate relationships. Rather than relying primarily on formal education or interpersonal networks, adolescents and young adults often prefer digital sources when seeking advice and information about sex and relationships. Platforms such as X, Instagram, and BlueSky provide perceived advantages of anonymity, autonomy, and accessibility, enabling users to engage in the de-identified sharing of sensitive concerns. In doing so, they contribute to the ongoing transformation of “romantic media ideologies,” understood as the taken-for-granted assumptions and discourses that shape how relationships are understood, evaluated, and experienced in contemporary societies. To date, much of the scholarship examining these dynamics has relied on qualitative methods such as interviews, ethnography, or discourse analysis. While such approaches offer valuable insights, they are limited in scope when considering the scale and complexity of digital interaction. Educational Data Science (EDS) offers a promising methodological framework to address this gap. By integrating Learning Analytics (LA) and Educational Data Mining (EDM), EDS provides robust tools for examining informal knowledge acquisition and meaning-making in online spaces. In this study, we apply three specific methods—social network analysis, natural language processing, and large language model annotation/classification—to analyze dating and relationship discourse on BlueSky, thereby extending EDS into a largely unexplored domain. Another dimension concerns the role of social media influencers as emerging “new experts” in the domain of dating and relationships. These figures act as knowledge brokers: they are perceived as credible and authentic, often combining entertainment with didactic or advisory content. At the same time, their interventions are not unproblematic, as advice can be contradictory, selective, and shaped by platform-specific logics of visibility, brand-building, and monetization. Our analyses identify three archetypal user groups—Knowledge-based Authority, Commercial Positioning, and Experiential Discourse. Each group demonstrates distinct communication styles, with varying degrees of formalized expertise and credibility claims. While all engage in advice-giving, their thematic emphases diverge, ranging from wellness and self-care to promotional strategies and lived relational experiences. By mapping these dynamics, the study contributes to scholarly debates on the evolution of romantic media ideologies and the social construction of expertise in digital discourse.